APPLICATION OF EUROPEAN UNION FISCAL RULES IN A CORONAVIRUS PANDEMIC CRISIS - Golubovic, Srđan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The paper examines the application of the European Union (EU) fiscal rules in the conditions of disturbances caused by the COVID-19 pandemic. Faced with a severe economic crisis, the European Union (EU) institutions for the first time activated a “general excape clause”, which allows for temporary deviation from the budgetary requirements, set by set by the Stability and Growth Pact in March 2020. The clause was introduced as part of the 2011 fiscal rules reform (six-pack) and allows member states to temporarily derogate from fiscal constraints due to severe economic disruptions. By activating the clause, the member states have been left with sufficient room for maneuver to take expansive fiscal policy measures, which mitigate the consequences of the crisis but also negatively affect the budget balance. Although conceived as a temporary deviation of fiscal indicators from the set values, in practice there was an extensive application of the general clause, which de facto led to the suspension of EU fiscal rules. This was also influenced by the decision of the European Commission and the Council of the EU to withdraw from initiating proceedings against member states with excessive budget deficits, due to the seriousness of the crisis and uncertainty regarding the recovery. Experience with the application of fiscal rules during the coronavirus pandemic crisis imposes the need to redefine the institutional framework of fiscal governance in the EU, which will ensure a stronger link between numerical constraints and fiscal policy objectives, but also provide enough space and resources for intervention during severe economic downturn.
Keywords: pandemic; economic crises; fiscal rules; Stability and growth pact